Investigation of Education in Latin America - Akkari, Abdeljalil; Pérez, Soledad (Education Policy Analysis Archives, 1999)
We consider Narodowski's reaction (1999) published by Education Policy Analysis Archives as Volume 7 Number 2 to be an invitation to a fruitful debate on education in Latin America. We want first to call attention to the fact that our original article—EPAA 6(7)—was not exhaustive; we never attempted to present all aspects of educational research in Latin America, an effort that would require the attention of several teams of researchers and numerous written works. Our objective, modest as it is, is to take a closer look at the evolution of educational research and to launch the debate on those aspects that seem to us high-priority for the region.